Genital tract screening finds widespread infection with mustelid gammaherpesvirus 1 in the European badger (Meles meles) - Kent, A; Ehlers, B; Mendum, T; Newman, C; Macdonald, DW; Chambers, M; Buesching, CD (Wildlife Disease Association, 2018)
Sexually transmitted diseases (STDs) can be important drivers of population dynamics because of their negative effects on reproduction. However, screening for STDs, especially in wildlife populations, is widely neglected. Using the promiscuous, polygynandrous European badger (Meles meles) as a model, we investigated the presence and prevalence of herpesviruses (HVs) in a wild, high-density population and assessed potential differences in somatic fitness and female reproductive condition between infected and uninfected individuals. We collected n=98 genital swabs from 71 females (51 adults and 20 cubs) and 27 males (26 adults and 1 cub) during spring and summer 2015. Using a PCR specific for a mustelid α-HV, all genital-swab samples tested negative. In a panherpes PCR, a γ-HV was found in 55% (54/98; 39 adults and 15 cubs), identified as mustelid gammaherpesvirus 1 (MusGHV-1) using DNA sequencing. This contrasts with the results of a previous study, which reported MusGHV-1 in 98% (354/361) of blood samples taken from 218 badgers in the same population using PCR. The detection of MusHV-1 in the female reproductive tract strongly indicates the potential for a horizontal and, likely also a vertical, route of transmission. Our results suggest a potential linkage of genital HVs and impaired future reproductive success in females, but because reproductive failure can have many reasons in badgers, the causative link of this negative relationship remains to be investigated.